Perception of Severity of Women at High Risk of Cervic Cancer About Cervic Cancer Screening Method IVA - Ulina Sagala, Hotma; Zuhriyah, Lilik; Agung Indrawan, I Wayan (Green Publisher Indonesia, 2022)
Cervical cancer is the fourth most common cause of cancer in the world in women. The high mortality rate is due to the low awareness of women doing early detection. Behavior can be influenced by threat assessment, one of which is perceived severity. The behavior of early detection of cervical cancer can arise due to the perception of the severity of cervical cancer. Women's concern and desire for early detection of cervical cancer is influenced by women's perceptions of cancer. This study aims to explore the perception of the severity of women at high risk of cervical cancer regarding cervical cancer screening using the IVA method. This type of research is a qualitative research with a descriptive phenomenological approach. The research sample used purposive sampling technique. The study was conducted from April to May 2022 in the working area of ​​the Ujung Batu Health Center, 10 participants were interviewed for 25-35 minutes. The variable in this study is the perception of the severity of cervical cancer screening using the IVA method. The instrument used in this study is an interview guide and analyzed by thematic analysis. The results showed that all participants knew that the severity of cervical cancer can harm women and can cause death. The conclusion is that the awareness of participants in cervical cancer screening is still lacking. All participants understand the severity and seriousness of cervical cancer but have not screened for cervical cancer yet.